Towards Marine Ecosystem-based Management in the Wider Caribbean - Fanning, Lucia; Mahon, Robin; McConney, Patrick (MARE Publication Series, 2011)
An approach that encompasses the human and natural dimensions of ecosystems is one that the Wider Caribbean Region knows it must adopt and implement, in order to ensure the sustainable use of the region's shared marine resources. This volume contributes towards that vision, bringing together the collective knowledge and experience of scholars and practitioners within the Wider Caribbean to begin the process of assembling a road map towards marine ecosystem based management (EBM) for the region. It also serves a broader purpose of providing stakeholders and policy actors in each of the world's sixty-four Large Marine Ecosystems, with a comparative example of the challenges and information needs required to implement principled ocean governance generally and marine EBM in particular, at multiple levels. Additionally, the volume serves to supplement the training of graduate level students in the marine sciences by enhancing interdisciplinary understanding of challenges in implementing marine EBM.